1999
DOI: 10.1039/a902952d
|View full text |Cite
|
Sign up to set email alerts
|

Coverage dependent behavior of redox reaction induced structure change and mass transport at an 11-ferrocenyl-1-undecanethiol self-assembled monolayer on a gold electrode studied by an in situ IRRAS–EQCM combined system

Abstract: The potential dependent structure change and mass transport at an 11-ferrocenyl-1-undecanethiol (FcC 11 SH) self-assembled monolayer on a gold electrode with various coverages were investigated by simultaneous Fourier transform infrared reÑection absorption spectroscopy (IRRAS) and electrochemical quartz crystal microbalance (EQCM) measurements in 0.1 M solution. As soon as the terminal ferrocene group was HClO 4 oxidized to a ferricenium cation (Fc`), a number of upward and downward IRRAS bands were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
123
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(137 citation statements)
references
References 36 publications
12
123
0
2
Order By: Relevance
“…For example, Collman et al 6 used ferrocene adsorption to demonstrate the applicability of Sharpless ''click'' chemistry as a general methodology for functionalizing surfaces coated with self-assembled monolayers. Chidsey and co-workers 2 studied co-adsorbed ferrocene and unsubstituted alkanethiol and observed the structural orientation/changes that accompany concentration changes; Aluletta et al 7 studied mixed SAMs of ferrocene-terminated thiols and hydroxyalkanethiols and proved the occurrence of phase separations; Ye et al 8 observed coverage-dependent behavior of the ferroceneterminated thiol SAMs induced by the redox reaction of the terminal ferrocene moiety, while Waldeck and co-workers showed how intermolecular electronic coupling pathways could contribute to the electron transfer; Uosaki and co-workers 10 studied SAM containing both ferrocene and azobenzene moieties and established how electro-and photochemical structural conversion of the cis and trans forms of the azobenzene moiety could impact on the charge-transfer processes; Crooks and co-workers 11 studied mixed monolayers of ferrocene-dendrimers and alkanethiols and, for the first time, introduced an elegant strategy for constructing an electrochemical current rectifier that permits current flow in only one direction; and Chambers et al 12 reported how a ferrocene-thiol SAM co-adsorbed with alkanethiolates could unravel nanoscale phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Collman et al 6 used ferrocene adsorption to demonstrate the applicability of Sharpless ''click'' chemistry as a general methodology for functionalizing surfaces coated with self-assembled monolayers. Chidsey and co-workers 2 studied co-adsorbed ferrocene and unsubstituted alkanethiol and observed the structural orientation/changes that accompany concentration changes; Aluletta et al 7 studied mixed SAMs of ferrocene-terminated thiols and hydroxyalkanethiols and proved the occurrence of phase separations; Ye et al 8 observed coverage-dependent behavior of the ferroceneterminated thiol SAMs induced by the redox reaction of the terminal ferrocene moiety, while Waldeck and co-workers showed how intermolecular electronic coupling pathways could contribute to the electron transfer; Uosaki and co-workers 10 studied SAM containing both ferrocene and azobenzene moieties and established how electro-and photochemical structural conversion of the cis and trans forms of the azobenzene moiety could impact on the charge-transfer processes; Crooks and co-workers 11 studied mixed monolayers of ferrocene-dendrimers and alkanethiols and, for the first time, introduced an elegant strategy for constructing an electrochemical current rectifier that permits current flow in only one direction; and Chambers et al 12 reported how a ferrocene-thiol SAM co-adsorbed with alkanethiolates could unravel nanoscale phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…The wave due to the redox of the ferrocene moiety decreased as the potential cycle was repeated and disappeared after about 20 cycles. These results show that the anodic current was due to both the formation of Au oxide and anodic oxidation of the SAMs at the GNC surface, which proceeds as follows [34]:…”
Section: Oxidative Desorption Of Sams From the Multilayer Of Pah/sam mentioning
confidence: 98%
“…When the potential was made more positive than that for the oxidative decomposition of the thiol SAM on gold [32][33][34][35], the SAM was gradually removed from the GNCs and GNCs started to aggregate [22,23].…”
Section: Introductionmentioning
confidence: 99%